Weight loss and sexual activity in adult obese individuals: Establishing a causal link - Arndt R. Reichert; Harald Tauchmann; Ansgar Wübker (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2015)
Obesity may not only be linked to undesirable health outcomes but also to limitations in sexual life. The present paper aims to assess whether there is a causal relationship between weight loss and sexual activity in adult obese individuals. To address the endogeneity of weight loss that is likely to result in biased estimation results, the analysis is based on data from a randomized field experiment. In this experiment financial weight-loss rewards were offered to a random subgroup of participants and can be used as exogenous source of weight variation in an instrumental variables approach. Estimation results indicate that for obese males loosing weight increases the probability for being involved in a sexual relationship. Conditional on having already lost some weight, a further reduction in obesity also increases the frequency of sexual intercourse. – – Übergewicht steht nicht nur im Zusammenhang mit Beeinträchtigungen im Gesundheitszustand, sondern ist auch mit Einschränkungen im Sexualleben assoziiert. Die vorliegende Arbeit analysiert, ob es einen kausalen Zusammenhang zwischen Gewichtsverlust und sexueller Aktivität bei erwachsenen übergewichtigen Personen gibt. Die Analyse basiert auf einem randomisierten Feldexperiment, um die Problematik der Endogenität des Gewichtsverlusts adäquat zu adressieren. In dem Experiment wurden finanzielle Anreize für eine zufällige Gruppe ausgelobt und als exogene Quelle von Gewichtsveränderung im Rahmen eines instrumentenvariablen Ansatzes verwendet. Die Schätzergebnisse zeigen, dass für übergewichtige Männer Abnehmen die Wahrscheinlichkeit erhöht, sich in einer sexuellen Beziehung zu befinden. Gegeben, dass bereits Gewicht abgenommen wurde, erhöht ein weiterer Rückgang des Übergewichts auch die Häufigkeit des Geschlechtsverkehrs.
Keywords: I10; I18; J28; J65; 330; obesity; sexual partnership; frequency of intercourse; randomized trial; weight-loss incentives